KŌICHI TANIGUCHI / SUNAKKU KENKYŪ-KAI (eds.): Nihon no yoru no kōkyō-ken: Sunakku kenkyū josetsu [The Public Sphere at Night-time in Japan: An Introduction to the Study of Sunakku) - Kozuka, Souichirou (Zeitschrift für Japanisches Recht, 2019)
Hakusuisha, Tōkyō 2017, 215 pp., Yen 1.900 zzgl. USt., ISBN: 9784560095478